A new species of Leucoagaricus (Agaricaceae) from Colombia - Ortiz, Adriana; Esperanza Franco-Molano, Ana; Bacci Junior, Mauricio [UNESP] (Mycotaxon Ltd, 2008)
A new taxon of Leucoagaricus is proposed as L. amazonicus. The collection representing this species was collected in the lowlands of the Amazonas Department, Colombia, on a dump produced by ants belonging to Acromyrmex octospinosus. The very particular habitat, the small size and dark brown basidiomata that stain yellowish when bruised, the peronate inferior annulus, and the cheilocystidia which are relatively short, capitate and filled with dense brown contents are some of the features of this species.
Keywords: Agaricales; taxanomy; Amazonia